Antifungal activity and GC-MS analysis of n-butanol extract of quinoa (Chenopodium quinoa Willd.) leaves - Khan, Iqra Haider; Javaid, Arshad (Bangladesh Journal of Botany, 2020)
Dry leaves of quinoa (Chenopodium quinoa Willd.) were extracted in methanol and its n-butanol fraction was separated. Solvent was evaporated and antifungal bioassays were carried out against Macrophomina phaseolina using different concentrations (1.562, 3.125, 6.25, 12.50, 25, 50, 100, 200 mg/ml) of the extract in malt extract broth. The entire set of concentrations significantly controlled the fungal growth. The lowermost concentration of the extract (1.562 mg/ml) reduced M. phaseolina biomass by 62% over control while all other concentrations completely controlled fungal growth. GC-MS analysis showed that there were 20 compounds in this fraction. Stigmasta-7,16-dien-3-ol was the predominant compound with peak area of 15.14% followed by 1-butanol, 3-methyl- (11.87%), β-sitosterol (9.93%), γ-sitosterol (8.84%), butane, 2-[1-methylethyl) thio]- (6.51%), cyclohexane, 1,1-dimethoxy- (6.27%), stigmasterol (5.98%) and stigmastanol (4.57%). The compounds such as 1-butanol, 3-methyl-; γ-sitosterol and stigmasterol present in n-butanol fraction of methanolic leaf extract of quinoa are highly and likely to be responsible for antifungal activity against M. phaseolina.